2022
DOI: 10.3390/coatings12040482
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Water Jet Erosion Performance of HVOF-Sprayed WC-10Co Coatings on 35CrMo Steel Utilizing Design of Experiments

Abstract: To enhance the surface of a material with the desired qualities for diverse applications in service, a variety of thermal and thermo-chemical surface treatment processes are used. Due to the high-velocity impact inherent in the process, high-velocity oxy-fuel (HVOF) spray is now frequently employed in industrial applications for its ability to generate a high-quality coating with appropriate hardness and low oxide content. In this investigation, a high-velocity oxy-fuel (HVOF) thermal spraying process was util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 68 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Also, varying the types of materials has a significant effect on the impact angle of erosion. Further, ductile materials are most susceptible to erosion at an impact angle of about 20°, but at a normal incidence angle, they exhibit high erosion resistance [11]. However, fragile materials are quickly destroyed when struck at an angle of 90°or higher, but when struck at a lower angle, they are impenetrable to erosion [12].…”
Section: Angle Of Impactmentioning
confidence: 99%
“…Also, varying the types of materials has a significant effect on the impact angle of erosion. Further, ductile materials are most susceptible to erosion at an impact angle of about 20°, but at a normal incidence angle, they exhibit high erosion resistance [11]. However, fragile materials are quickly destroyed when struck at an angle of 90°or higher, but when struck at a lower angle, they are impenetrable to erosion [12].…”
Section: Angle Of Impactmentioning
confidence: 99%
“…Quaisie et al [16] demonstrated through experiments that when the jet pressure is below 20 MPa, the surface forming depth and surface roughness of the water jet erosion materials increase with the pressure. Ribu et al [17] systematically investigated the erosion rate by considering water jet parameters such as the impact angle, water jet velocity, distance, and erosion flow and concluded that the impact angle has the greatest impact on the coating erosion rate and that the influencing factors include the water jet velocity, distance, and erosion flow. Zhao et al [18] investigated the erosion failure mechanism of different impact angles through an experiment on the abrasive jet erosion of 316 stainless steel and considered that the small-angle erosion was mainly plowing, while the large-angle erosion was a mostly positive collision.…”
Section: Introductionmentioning
confidence: 99%